The concentration and separation of polysaccharides from Ecklonia maxima extracts using ultrafiltration membranes - Cilliers, Ryan Christopher (Stellenbosch : Stellenbosch University, 2025)
Cilliers, R. C. 2025. The concentration and separation of polysaccharides from Ecklonia maxima extracts using ultrafiltration membranes. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/da2f0b19-0db8-4bf6-82be-aa7815f286c7